(untitled) (Biological Sciences - PJSIR, 1995)
Polarized microscopycanbe used forsemi-quantitativedetermination ofcrystalorientation. Due todifference in colour or grey contrast, polarized microscopycan beused to identify inclusions, and nucleating grains in the study of deformation and recrystallization processes. The usefulness of polarized microscopy has been demonstrated which shows microstructural features of various levels of grey colour contrast due to orientation differences. An X-ray OrientationDistributionPlot(ODF)isalsopresentedtosubstantiatetheinferernesdrawnonthebasisof metllographic examination.